Investigating priority service attribute for online travel agencies (OTA) mobile app development using AHP framework - Tutur Wicaksono; Csaba Bálint Illes (Journal of Tourism and Economic, 2022)
This study aims to identify service priority attributes for online travel agency (OTA) mobile application development. A quantitative- descriptive research design was used in this study. Data collection was done through literature review and questionnaire surveys. The respondents in this study were 273 customers of OTA. The results showed that the service attribute with the highest importance was the fulfilment dimension with an average weighting of 4.84 out of 5. In the fulfilment dimension, the service attribute with code F3, which refers to the need for mobile applications to be able to deliver orders as quickly as possible, has the highest weight. In second place is the privacy dimension, with an average importance score of 4.80. In this dimension, service attribute P3, which refers to the ability of mobile applications to protect customers' credit card data, ranks first. In third place is the responsiveness dimension with an average importance value of 4.69. Attributes relating to the customer being able to speak directly to customer service in the event of problems are the attributes with the highest weighting on the responsiveness dimension.